Artificial Hypothermia in Modern Reanimatology - L. V. Usenko; A. V. Tsarev (Общая реаниматология)
The paper covers the present ideas on the mechanisms of neuroprotection, indications for and contraindications to the clinical application of therapeutic hypothermia, possible complications, as well as the future areas of its use in intensive care. Key words: therapeutic hypothermia, ischemic-reperfusion lesion, critical conditions.